Feminist Hermeneutics of Fatima Mernissi and a Discourse Analysis of Aurat in the Indonesian Context - Rizkiyah, Sahilah; Huda, Solihul; Anam, Khoirul (Prodi Studi Agama-Agama, 2026)
This study examines the concept of women's aurah in Islam through the thought of Fatimah Mernissi by placing it within the framework of Michel Foucault's discourse analysis. This research aims to analyze how Mernissi reconstructs the understanding of aurat through a hermeneutical-feminist approach and examine the relevance of her thinking in the context of Indonesian Islam. The method used is a qualitative approach with library research, through systematic discourse analysis, including the identification of the formation of the discourse of the interpretation of the aurat, the analysis of the power-knowledge relationship, and the reading of Mernissi's thought as the object of discourse. The results of the study show that aurat can be understood as a discursive construct created through the legitimacy of religious interpretation and negotiated in the dynamics of the Islamic women's movement in Indonesia. Therefore, the concept of aurah not only serves as a theological standard, but also as a place where meaning is created and resolved in modern Islamic discussions